AN ANALYSIS OF QUESTIONING STRATEGIES IN A PUBLIC SENIOR HIGH SCHOOL IN BANDUNG - Yuli Puspita Sari, - (2011)
ABSTRACT This study entitled "An Analysis of Teacher's Questioning Strategies in a Public Senior High School in Bandung" was aimed to investigate: (1) the teacher's questioning strategies in the classroom, (2) the teacher's rationale in employing the strategies, (3) the most helpful strategies for the learners. This study was conducted qualitatively involving an English teacher and 38 tenth graders. The data were obtained from video-recording and interview. The data from video-recording and interview were transcribed, coded, analyzed, and interpreted. The findings showed that the teacher employed some questioning strategies namely blank-filling, repetition, rephrasing, simplification, exemplification, code-switching, and wait-time. Based on the findings, the teacher frequently used the blank-filling strategy in eliciting learners' responses. However, sometimes this strategy was not effective to be applied for senior high school learners. Meanwhile, the teacher's rationale in employing these strategies were based on three aspects, (1) the characteristics of the learners, (2) the teacher's understanding about questioning strategies, and (3) the goals of teaching. Furthermore, the learners considered that code-switching, exemplification, and wait-time to be the most helpful strategies in supporting their learning. It was concluded that the teacher was aware of the strategies in eliciting learners' responses toward his question. The teacher, however, practically could not perform some strategies well. It is recommended for teachers to employ the questioning strategies in their teaching, since the strategies may encourage learners to be active in the classroom.